Knowledge and approach to first aid in the school environment: education in health and nursing (Research, Society and Development, 2023)
Objectives: to understand the knowledge that school employees have about first aid and to promote educational first aid actions for these professionals. Methodology: study based on Research-Action, carried out with 25 employees of an elementary school located in the city of São Fidélis. Results: most participants showed little security, skill and knowledge to deal with first aid situations and the minority had the opportunity to train themselves with courses on first aid before, which further boosted the realization of educational actions. The actions had a verbal approach and practical demonstrations, such as simulations. Conclusion: it is necessary that the employees of schools, public or private, have knowledge about first aid, try as much as possible to prevent it from happening and know what to do in case of accidents. This research approached the Lucas Law with the performance of educational actions by undergraduate nursing students, but it was not configured as a technical training itself. Health education plays a fundamental role in the professional practice of nurses, promoting care and demonstrating skills in the role of educator, within the legal aspects.